Long‐Term Antihyperalgesic and Opioid‐Sparing Effects of 5‐Day Ketamine and Morphine Infusion ("Burst Ketamine") in Diabetic Neuropathic Rats. Issue 9 (20th March 2015) - Mak, Plato; Broadbear, Jillian H.; Kolosov, Anton; Goodchild, Colin S.
Abstract: Background: "Burst ketamine" (BK) is the long‐term infusion of subanesthetic ketamine in combination with an opioid. It is used clinically with mixed success to provide long‐term pain relief and improve opioid response in patients. BK has not been simulated preclinically, therefore, its effectiveness was investigated in an animal model of neuropathic pain—streptozotocin‐induced diabetic neuropathy. Methods: Diabetic neuropathic rats were randomized to receive a subcutaneous infusion of ketamine 20 mg/kg/day plus morphine 20 mg/kg/day (BK), either drug alone at the same dose, or sham treatment. Drugs were administered continuously over 5 days via osmotic minipump. Antihyperalgesic effects and antinociceptive responsiveness to morphine (0.625–10 mg/kg, i.p.) were assessed at 2, 4, 6, and 12 weeks post‐treatment using paw withdrawal latency (PWL) from noxious heat (thermal hyperalgesia) and mechanical touch (tactile allodynia). Results: Antihyperalgesic effects with significant increases in PWL from noxious heat occurred following BK and ketamine‐only infusion, persisting 12 and 4 weeks, respectively. Opioid‐sparing effects from noxious heat with increased sensitivity to morphine analgesia also occurred for 6 weeks after BK and 2 weeks after ketamine treatment; acute treatment with the maximum nonsedating dose of morphine (5 mg/kg) produced an antinociceptive effect in these two groups, but not in sham‐treated rats. In morphine‐only infusion rats, hyperalgesia and opioid insensitivity were both increased. Conclusions: This is the first preclinical study to use a model of neuropathic pain to demonstrate the utility of the BK procedure for delivering a long‐lasting reduction in hyperalgesia and improved antinociceptive responsiveness to opioids.